TEACHERS AND TEACHING METHOD: THE EFFECTS ON LEARNING FOR SUSTAINABLE DEVELOPMENT - Lawal, Suleiman; Ishaq, Nuhu Jaafar (Sokoto Educational Review, 2020)
This Paper examines the challenges teachers face in the selection and use of teaching methods, and the effects of these teaching methods on learning for sustainable development. Six (6) widely used teaching methods were explained. They include: Lecture/telling method, Discussion method, demonstration method. Assignment method, play way method and finally Question and answer method. The effects of the above mentioned methods on learning both positive and negative were also explained. The writers explained how the effects of teaching methods on learning could lead to sustainable development. Finally, conclusion was drawn by the writers and recommendations were made based on the discussion made.